Developing a Software Tool to Calculate and Classify the Roughness of the Earth’s Surface Using MATLAB - دالي كنان; ديوب وائل; شعبان فادي (Latakia University Journal -Engineering Sciences Series, 2023)
This article reviews the general concept of the roughness of the topographic surface, as there are many scientific concepts that dealt with this term, but most of them agree that it is the amount of difference in heights from the average height. Great in hydrological and geological studies, such as determining the abundance of flow, in addition to giving an image of the geological layers. This research dealt with how to digitally express ruggedness in a suitable software environment, namely MATLAB, within a study area extending from Salah al-Din Castle in the west to the Slenfeh region in the east. It depends on the average inclinations, bearing in mind that both coefficients produce a chart that expresses the varying degrees of ruggedness within four different levels (level, moderately rugged, very rugged, and very rugged). 4.4% for the third level, and 0.73% for the fourth level, compared to the average propensity coefficient, which gave 55.68% for the first level, 26.45% for the second level, 17.48% for the third level, and 0.39% for the fourth level. This research will help the engineers to classify the areas in order to identify the difficulties that the surveyors may face in that area.